Sosialisasi Pentingnya Surat Pemberitahuan Tahunan (SPT) Pajak di Rumah Sakit Elisabeth Semarang: Socialization of the Importance of Annual Tax Returns (SPT) at Elisabeth Hospital in Semarang - Rikki Marendra (Experimental Student Experiences, 2022)
Tax reporting is one of the important activities required by the Ministry of tax and finance to make the public aware that in this socialization it is health workers, but unfortunately there are still many health workers who do not understand how to report Annual SPT online. This socialization has the following objectives: 1) to educate health workers about the importance of annual tax reporting; 2) provide a way of how to report tax steps in the e-filling application; 3) forwarding information and socialization from the Directorate General of Taxes (DJP) of the Republic of Indonesia to health workers regarding state revenues through taxes. The method used in conducting this socialization is an online learning method where participants can interact directly with resource persons to ask questions about filling out the Annual Electronic Tax Return, the socialization will be held on Wednesday, March 2, 2022 with 100 participants from health workers. By using a practical model, participants felt that they were gaining knowledge directly and 82% of them were able to do tax reporting online and independently.